Exploring RAB11A Pathway to Hinder Chronic Myeloid Leukemia-Induced Angiogenesis In Vivo - Roma-Rodrigues, Catarina (2023)
project LA/P/0140/2020 of the Associate Laboratory Institute for Health and Bioeconomy—i4HB. This work is also funded by Fundação para a Ciência e Tecnologia in the scope of the project 2022.04315.PTDC. Publisher Copyright: © 2023 by the authors.